Biosilicate® Glass-Ceramic Foams From Refined Alkali Activation and Gel Casting - Bernardo, Enrico; Elsayed, Hamada; Romero, Acacio Rincon; Crovace, Murilo C.; Zanotto, Edgar D.; Fey, Tobias (Frontiers in Materials, 2021)
Biosilicate® glass-ceramics are among the most valid alternatives to 45S5 Bioglass. They combine a similar bioactivity and bioresorbability as the 45S5 with superior mechanical strength, owing to the crystallization of a Na–Ca silicate phase. This crystallization may be experienced upon viscous flow sintering of fine glass powders, thus configuring a sinter-crystallization process. As crystallization is seldom complete, sintering can also be applied to semicrystalline powders. The sintering/crystallization combination may be exploited for shaping highly porous bodies, to be used as scaffolds for bone tissue engineering, in the form of foams. The present study aims at exploring a gel-casting process, based on the room temperature foaming of powders suspended in a “weakly alkaline” (1 M NaOH) aqueous solution, followed by sintering at 1,000°C. The gelation of suspensions is attributed to the formation of hydrated compounds, later decomposed upon firing. Amorphous powders provided more intense gelation than semicrystalline ones, promoted a more homogeneous foaming, and stimulated a substantial crystallization upon firing. The homogeneity of foamed samples was assessed using micro-tomography and was further improved by casting foamed suspensions (“foam casting”) before setting.
CRIS-Team Scopus Importer:2021-04-09
Keywords: alkali activation; foams (froth); gel casting; glass-ceramics; sintering